IBM DS8910F Model 993 Rack Mounted Storage System - Brunson, Sherry; Dufrasne, Bertrand; Kimmel, Peter (IBM Redbooks, 2020)
This IBM® Redpaper publication presents and positions the DS8910F Model 993. The modular system can be integrated into 15U contiguous space of an IBM z14® Model ZR1 (z14 Model ZR1), IBM LinuxONE Rockhopper II (z14 Model LR1), or other standard 19-inch wide rack. The DS8910F Model 993 allows you to take advantage of the performance boost of all-flash systems and advanced features while limiting datacenter footprint and power infrastructure requirements.